Responding to the Current Capricious State of Australian Educational Leadership: We Should Have Seen It Coming! - Christopher M. Branson; Maureen Marra; Paul Kidson (MDPI AG, 2024)
The capricious state of Australian educational leadership is evidenced in the publication, "The Australian Principal Occupational Health, Safety, and Wellbeing Survey 2022 Data", which highlights unsustainable adverse health outcomes for an increasing number of school leaders. According to this report, the accumulation of stress caused by the sheer quantity of work, the lack of time to focus on teaching and learning, a lack of sufficient teachers, and having to care for an increasing number of staff and students with mental health issues were the main causes of professional disillusionment and burnout among Australian school leaders. Moreover, the level of destabilisation and chaos that this situation could cause, should it continue to rise, is compounded by current research highlighting an ever-decreasing number of applicants for school leadership positions. To assign blame for this serious predicament on the excessive school leadership demands during COVID-19 is to ignore the abundant pre-existing evidence already pointing to this eventuality. However, the way in which Australian school leaders were able to constructively lead during the intensely demanding COVID-19 period does provide additional compelling support for the adoption of a far more relational foundation for leadership theory and practice. Hence, in response to this understanding, this article first presents during-COVID-19 and pre-COVID-19 Australian school leadership research literature to not only describe the evolving concerning issues but also to present the demand for a more relational approach to leadership. Then, the article proceeds to justify and illustrate a new relational approach to the practice of school leadership informed by our theory of organizational ecology. It is proposed that this new way of leading relationally will enable Australian school leaders to ultimately overcome the myriad of complex and stressful crises that now confront them.